Posisi Al-Qur`an DalamIntegrasi Ilmu : Telaah Terhadap Pemikiran Kuntowijoyo dan M. Dawam Rahardjo - Wardani Wardani (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2018)
The integration of knowledge has become a central issue emerging among scholars in Indonesian Islamic universities. Some ideas have been proposed to make “bridge” between religious and secular knowledge, as we can see, for instance, in the thought of Kuntowijoyo on “prophetic social sciences”, M. Dawam Rahardjo on “decolonization of social sciences”, M. Amin Abdullah on “spider web of knowledge”, and Mulyadhi Kartanegara on “holistic reconstruction of knowledge”.The researches conducted so far have not touched the core problem in all these proposed ideas yet, namely the place of the Qur`an as a revelation in the integration of knowledge. In fact, the Qur`an constitutes a source of knowledge and, at the same time, an inspiring and guiding scripture, for Moslem’s beliefs, praactices, and thought. Therefore, neglecting the Qur`an in constructing Moslem’s thought on the integration of knowledge will make our understanding the issue artificial. The present article is aimed at studying the thought of Kuntowijoyo and M. Dawam Rahardjo by focusing the discussion on main points: firstly, on the place the Qur`an in the integration of knowledge (as inspiration,source of knowledge, or starting point in building theory) (and the present author will describe data as they are); secondly, intellectual and social background that play important role behind the ideasand modes of use of the Qur`an for intellectual enterprises (and the present author will go into deep analysis on factors or contexts in which the ideas formed); thirdly, the originality, strength, and weakness of the ideas (and the present author will examine the ideas in accordance with some standards).